Research advances in the molecular regulatory mechanisms of fruit coloration in fruit trees - MA Shurui; CHI Fumei; SONG Yang (Guoshu xuebao)
The color of fruit is one of the core indicators for judging fruit maturity and a necessary condition for evaluating fruit quality, which greatly promotes consumers' purchasing intention and market competitiveness. Traditional cultivation methods have disadvantages such as long cycles and limited effects on targeted trait improvement. Therefore, new gene editing techniques and multi-omics combined analysis (metabolomics, transcriptomics, and proteomics) are being widely used. Whether molecular marker-assisted breeding can be used to precisely and directionally regulate fruit color is a current research focus and a future research direction. Fruit coloring mainly relies on the dynamic balance among three types of pigments, namely carotenoids, anthocyanins, and chlorophylls, in the fruit of fruit trees, involving complex metabolic regulatory networks and multi-pathway interactions. This paper focuses on summarizing the changing trends of the three types of pigments during fruit coloring and classifying the molecular mechanisms involved in environmental factors, gene regulation, and epigenetic levels that affect fruit coloring. Carotenoids give fruits yellow, orange, red, and purple colors due to the conjugated double bonds in their polyene chain. Besides their coloring function, they also have photoprotective, antioxidant, and plant hormone precursor (ABA) synthesis functions. The key enzymes involved in their metabolic pathways mainly include PSY, PDS, ZDS, CHYB, LCYb, and LCYe. The synthesis of carotenoids is regulated by both environmental and transcription factors. Environmental factors mainly include light, temperature, and the application of exogenous plant growth regulators. For temperature, low temperature during storage can promote the synthesis of carotenoids in citrus peels (CcPSY2, CcCHYB, and CcZEP), but the upregulation of chlorophyll cycle genes may also mask the coloring of carotenoids, resulting in uncolored peels. However, under cultivation conditions, low temperature affects the absorption of nitrogen in the soil and activates the transcriptional activity of related synthesis genes. Exogenous plant growth regulators commonly used include ethylene, abscisic acid (ABA), and methyl jasmonate (MeJA), all of which significantly regulate the expression of metabolism-related genes. Transcription factors mainly involve MADS-box, NAC, MYB, and bHLH, which complete the synthesis or degradation of carotenoids through interactions with metabolic genes. In addition, transcription factors related to hormone signal transduction pathways, such as AP2/ERF, can also interact with MADS-box and other transcription factors. The molecular regulatory mechanism of anthocyanin synthesis has been well studied. Their biosynthesis is dominated by the MYB-bHLH-WD40 (MBW) complex, and the key enzymes mainly include PAL, CHS, CHI, F3H, DFR, ANS, and UFGT. The MYB family, along with bHLH and WD proteins, forms the transcriptional regulatory network that activates structural genes such as ANS and UFGT. NAC and bZIP enhance regulatory complexity through cross-pathway interactions. The interaction of light and temperature in environmental regulation and the accumulation of anthocyanin content under drought and other stresses significantly enhance the plant's resistance to stress environments. The regulatory pathways of exogenous plant growth regulators are relatively complex. On the one hand, application can directly regulate transcription factors and indirectly activate or inhibit the expression of genes related to the anthocyanin metabolic pathway. On the other hand, the application of exogenous regulators can change the interaction network between the receptors of various endogenous hormone signaling pathways and the MBW complex or other transcription factors. Under the combined action of internal and external hormones, the efficiency of pigment accumulation can be significantly improved. In epigenetics, long-chain noncoding RNAs (lncRNAs) and microRNAs (miRNAs) play a significant role in the accumulation of anthocyanins by regulating transcription factors or chromatin remodeling to influence anthocyanin metabolism. Chlorophyll plays a core role in photosynthesis, and it also has antioxidant, anti-inflammatory, anti-cancer and anti-obesity medical and health care functions. Its metabolism is regulated by the dynamic balance of synthesis (GluRS, POR, and CAO) and degradation (PAO, SGR, and PPH) pathways to control fruit de-greening. The transcription factor regulation of chlorophyll includes gene families such as GOLDEN2-LIKE (GLK), MYB, NAC, bHLH and APRR. Among them, the GLK family (kiwifruit AchGLK and apple MdGLK1) is considered a core regulatory factor for chloroplast development and can jointly regulate chloroplast development and the gene expression of chlorophyll synthase with MYB. Transcription factors related to hormone signal transduction, such as AP2/ERF, mediate de-greening by binding to the promoters of PPH and PAO. The most important environmental factor, light conditions, can induce endogenous ethylene signals to mediate chlorophyll degradation. Different light quality regulation mechanisms also vary. In addition, the regulation of chlorophyll metabolism by environmental factors is particularly special in the case of metal ions, and the gene expression of ion transport proteins is crucial. The gene expression of grape Fe2+ transporter VvIRT and peach peel Mg2+ transporter PpMGT has been studied. DNA hypomethylation in epigenetic regulation leads to abnormal chloroplast development in pineapples, and the reduction of methylation levels in citrus and strawberries inhibits the expression of chlorophyll synthesis genes. Currently, there is a lack of systematic and in-depth analysis of the temporal sequence of chlorophyll and carotenoid accumulation during fruit ripening, the competitive synthesis of anthocyanins and carotenoids, and the synergistic or antagonistic effects among the three. Revealing the key nodes of cross-pathway metabolism, such as the common transcription factors MYB, bHLH and NAC, is beneficial for the global regulation of pigment metabolism. At present, the interaction mechanism between epigenetics and hormone signals is still unclear, and the molecular mechanism by which environmental stress (such as low temperature and drought) regulates pigment metabolism through epigenetic means also needs further study. This is an important direction for improving the stress resistance of fruit trees. Based on the existing molecular mechanisms, the accumulation of fruit pigments can be directly regulated, and a coordinated interaction model of light quality, temperature and hormones can be established in facility cultivation to maximize the accumulation of fruit pigments. Fruit color is not only an appearance indicator but is also closely related to nutritional value, storability and stress resistance. In the future, it is necessary to explore the relationship between the fruit color regulation network and the comprehensive quality of fruit, so as to meet market demands and efficiently cultivate high-quality fruit tree varieties.